Assessment of Sexual Functions in Male Patients with Ankylosing Spondylitis Compared with Healthy Controls - Aylin REZVANİ and Şeniz ÖK and Saliha Eroğlu DEMİR1 (Archives of Rheumatology, 2012)
Objectives: This study aims to investigate the impact of ankylosing spondylitis (AS) on sexual functions in male patients, to compare the results with healthy male controls, and to identify the associations with disease-related variables. Patients and methods: A total of 39 male patients with AS (mean age 38 years; range 27 to 52 years) and 27 healthy male subjects (mean age 30 years; range 23 to 45 years) were included in the study. The Bath Ankylosing Spondylitis Metrology Index (BASMI), the Bath Ankylosing Spondylitis Functional Index (BASFI), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Short Form 36 (SF-36) and the Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire were used for those with AS, while the International Index of Erectile Function (IIEF) and the Beck Depression Inventory (BDI) were utilized for all the study subjects. Results: The frequency of erectile dysfunction in the male patients with AS and the healthy controls was 43.6% and 51.9%, respectively. No statistically significant differences were found with regard to demographic characteristics, the IIEF, or the BDI scores between the two groups (p>0.05). No significant correlation was found between any domain of the IIEF and the AS indices or laboratory parameters. However, erectile function, overall satisfaction, the total IIEF, and the level of erectile dysfunction were found to be correlated with the BDI. Conclusion: Sexual dysfunction is common in male patients with AS; however, we could not find any statistically significant differences between them and the healthy male controls in terms of sexual functions. Sexual dysfunction in male patients with AS seems to be associated with an unfavorable psychological status.